QUALITATIVE DESCRIPTIVE RESEARCH: INTEGRATING INQUIRY-BASED LEARNING INTO ELEMENTARY SCHOOL ENGLISH INSTRUCTION - Nirwan, Nirwan; Faudi, Faudi; Isra, Rahmi; AG, Burhanuddin (English Education Department, 2024)
This study is a qualitative descriptive research that focuses on integrating Inquiry-Based Learning (IBL) into the teaching of English in elementary schools in Indonesia. The research methodology includes interviews with teachers, classroom observations, and analysis of curriculum documents. The aim is to explore the challenges, experiences, and perceptions of implementing IBL approaches. It highlights the potential benefits of IBL, such as increased student engagement and language proficiency, but also identifies challenges, such as limited resources and varying levels of teacher readiness. The research emphasizes the importance of addressing these challenges while leveraging the potential benefits of IBL to create enriching learning experiences for students. The study's practical implications are discussed, focusing on enhancing English instruction practices in elementary schools. It emphasizes the need for comprehensive professional development, supportive classroom environments, and curriculum alignment. This research provides insights into IBL implementation in the Indonesian context and contributes to the ongoing discourse on effective English language education.